New approach against Sybil attack in wireless sensor networks - FENG Tao1; MA Jian-feng2 (Tongxin xuebao)
A particularly harmful attack against many sensor network applications is known as the Sybil attack.A novel approach which is sensor node identity witness information validation for random secret information predistribution to defend against the Sybil attack was proposed,and their comprehensive performance was analyzed.In random secret in-formation predistribution,new secret information assignment schemes were proposed and assign a random set of key-related information to each sensor node based on one-way accumulators.In the common keys set-up phase,node-to-node identity witness authentication and key exchange protocols（IDW-AKE）which are provably secure against the active adversaries in universally composable model was proposed.Using IDW-AKE protocols,each node can com-pute the unique common keys it shares with its neighbors.